2021
DOI: 10.2196/29990
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Health Information Technology Use Among the US Population With and Without Cardiovascular Risk Factors, 2012-2018: Evidence From the National Health Interview Survey

Abstract: Background The COVID-19 pandemic has required clinicians to pivot to offering services via telehealth; however, it is unclear which patients (users of care) are equipped to use digital health. This is especially pertinent for adults managing chronic diseases, such as obesity, hypertension, and diabetes, which require regular follow-up, medication management, and self-monitoring. Objective The aim of this study is to measure the trends and assess factors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
(21 reference statements)
2
8
0
Order By: Relevance
“…Demographic data indicated that the majority of website users were white women with higher education aged between 20 and 59 years. This is consistent with the findings of other studies that females and adults aged 18-64 years, with high levels of socioeconomic status, are more engaged, than males and other age groups, in using health content-related websites [39,[48][49][50][51][52][53][54]. The website's reach may be a reflection of recent evidence showing that women perceived a decline in their mental health in 2020 during the second wave of the pandemic and experienced worse mental health outcomes in comparison with men [1,25,40,55].…”
Section: Principal Findingssupporting
confidence: 92%
“…Demographic data indicated that the majority of website users were white women with higher education aged between 20 and 59 years. This is consistent with the findings of other studies that females and adults aged 18-64 years, with high levels of socioeconomic status, are more engaged, than males and other age groups, in using health content-related websites [39,[48][49][50][51][52][53][54]. The website's reach may be a reflection of recent evidence showing that women perceived a decline in their mental health in 2020 during the second wave of the pandemic and experienced worse mental health outcomes in comparison with men [1,25,40,55].…”
Section: Principal Findingssupporting
confidence: 92%
“…Female sex was associated with increased eHealth usage. The uptake of eHealth tools among females is concordant with a large body of research showing they have higher eHealth usage 28,34,46 . This may be due to higher levels of health care engagement and management among female patients, who tend to be more involved not only in self‐care but also in the care of their family members 28 .…”
Section: Discussionsupporting
confidence: 57%
“…The uptake of eHealth tools among females is concordant with a large body of research showing they have higher eHealth usage. 28,34,46 This may be due to higher levels of health care engagement and management among female patients, who tend to be more involved not only in self-care but also in the care of their family members. 28 Increasing age, higher education, and ability to use the internet independently were positively associated with patient portal and eHealth use.…”
Section: Discussionmentioning
confidence: 99%
“…In a national longitudinal study by Clark et al 200 , the average 30-year risk of developing CVD for young adults (mean age=29) ranged from 4.4-18%. Health literacy and education initiatives 199 , 201 , 202 that emphasize CVD prevention (e.g. healthy diets, physical activity, avoiding substance use) and the recognition of cardiovascular events need to be developed and targeted at emerging adults and parents/guardians.…”
Section: Discussionmentioning
confidence: 99%